Reconstructive surgery of the rectum, anus and perineum - Madoff, Robert D.; Wexner, Steven; Zbar, Andrew P. (Springer London, 2013)
Reconstructive Surgery of the Rectum, Anus and Perineum provides the reader with a didactic discussion of complex problems which require re-operative surgery; including details of preoperative investigation, postoperative follow-up and a detailed operative approach. This comprehensive and detailed text uses a formulated algorithm approach to these complicated cases using operative photographs and composite explanatory line drawings which complement 'how-to' guides in describing the operative technical tips and pitfalls from experienced commentators. Reconstructive Surgery of the Rectum, Anus and Perineum, is written by leading world experts in the field of colorectal surgery and is a valuable and timely resource for colorectal surgeons and colorectal trainees alike. In addition, general surgeons will be interested in the specialist nature of dealing with difficult colorectal complications dealt with in this unique textbook.